Pemanfaatan E-Commerce dan Pengetahuan Akuntansi: Dampaknya terhadap Kinerja UMKM - Sabila, Rohadatul; Fajar Syaiful (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to examine the impact of e-commerce adoption and accounting knowledge on the performance of MSMEs in the digital economy. A quantitative approach was applied, with 120 questionnaires distributed to MSME respondents and data analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results reveal that e-commerce adoption significantly improves MSME performance by enhancing operational efficiency, market reach, and customer engagement. Accounting knowledge also positively influences performance, although its effect is relatively smaller compared to e-commerce adoption. These findings emphasize the importance of combining technological adoption with financial literacy to strengthen business operations. Theoretically, the study contributes empirical evidence regarding the role of digital tools and accounting competence in improving MSME efficiency and competitiveness. Practically, it suggests that enhancing digital skills and accounting knowledge can serve as strategic measures for MSMEs to achieve sustainability and maintain a competitive advantage in an increasingly digitalized business environment.